Culturally Sustaining Pedagogy in Elementary Social Attitude Formation: Culturally Sustaining Pedagogy Dalam Pembentukan Sikap Sosial Sekolah Dasar - Khusnul Phathona; Agus Basuki (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Elementary education in multicultural societies requires pedagogical approaches that address cultural diversity while supporting social attitude development. Specific Background: Culturally Sustaining Pedagogy positions students’ cultural identities as central resources within learning processes and school culture. Knowledge Gap: Limited empirical studies document how this pedagogical approach is practiced holistically in Indonesian elementary schools and how it relates to students’ social attitudes. Aims: This study examines the application of Culturally Sustaining Pedagogy, the roles of school leaders and teachers, and implementation constraints in shaping students’ social attitudes at SD Pedagogia Labschool FIP UNY. Results: Using a qualitative case study design, findings indicate that culturally based learning activities and school programs are integrated across classroom instruction and daily practices, fostering empathy, cooperation, tolerance, and mutual respect among students from diverse backgrounds. School principals contribute through policy formulation and cultural school leadership, while teachers function as facilitators and role models of social values. Identified constraints include limited instructional time and diverse student characteristics, addressed through adaptive time management, collaborative teaching, and reinforcement of school culture. Novelty: This study presents a comprehensive illustration of culturally sustaining practices embedded simultaneously in curriculum, school programs, and institutional culture at the elementary level. Implications: The findings provide practical reference for developing culturally grounded learning models that support social attitude formation within multicultural elementary education contexts. Highlights • Integration of culture-based learning practices supports daily social interaction among diverse students• School leadership and teacher collaboration sustain culturally grounded educational practices• Institutional culture functions as a medium for social attitude development in elementary education Keywords Culturally Sustaining Pedagogy; Social Attitude Formation; Multicultural Elementary Education; School Culture; Qualitative Case Study